Blow-up the symmetry analysis for the Hirota-Satsuma equations - H. A. Zedan (Հայաստանի ԳԱԱ)
The paper investigates the invariance and integrability properties of Hirota-Satsuma equations. Painleve analysis for the general similarity reduced ordinary differential equation is performed. Using Rung-Kutta-Merson method in shooting and matching technique, the nonlinear ordinary differential equations are solved that were numerically converted from similarity reduction.
Keywords: Science; Mathematics